2021
DOI: 10.1111/rda.14006
|View full text |Cite
|
Sign up to set email alerts
|

Periplaneta americana peptide decreases apoptosis of pig‐ovary granulosa cells induced by H2O2 through FoxO1

Abstract: Oxidative stress can induce apoptosis of granulosa cells and lead to follicular atresia, thereby reducing the number of pigs giving birth. The aim of this study was to investigate the protective effect of Periplaneta americana peptide (PAP) on the apoptosis of the granulosa cells of pig ovaries (PGCs) induced by hydrogen peroxide (H 2 O 2 ) via FoxO1. PGCs were treated with H 2 O 2 to establish a cell apoptosis model. Cell viability was measured using the cell counting kit-8 (CCK-8) assay, and cell apoptosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Modern medicine has further studied Periplaneta americana extract and found that it possesses several outstanding biological properties, including antibacterial, antioxidant, anti-inflammatory, and anti-cancer properties [129,130]. It has been demonstrated that Periplaneta americana peptide can significantly inhibit H 2 O 2 -induced apoptosis in KGN cells and porcine ovarian GCs by upregulating SIRT1 expression and reducing FOXO1 expression [73,131,132]. Moreover, Periplaneta americana peptide can also inhibit mitochondrial damage by upregulating Bcl2L13-mediated mitochondrial autophagy, thereby suppressing OS-induced apoptosis in KGN cells [107].…”
Section: Periplaneta Americana Peptidementioning
confidence: 99%
“…Modern medicine has further studied Periplaneta americana extract and found that it possesses several outstanding biological properties, including antibacterial, antioxidant, anti-inflammatory, and anti-cancer properties [129,130]. It has been demonstrated that Periplaneta americana peptide can significantly inhibit H 2 O 2 -induced apoptosis in KGN cells and porcine ovarian GCs by upregulating SIRT1 expression and reducing FOXO1 expression [73,131,132]. Moreover, Periplaneta americana peptide can also inhibit mitochondrial damage by upregulating Bcl2L13-mediated mitochondrial autophagy, thereby suppressing OS-induced apoptosis in KGN cells [107].…”
Section: Periplaneta Americana Peptidementioning
confidence: 99%